Membangun Fondasi Perubahan: Pengaruh Perceived Organizational Support terhadap Readiness for Change Karyawan PT X - Dirgantara, Muhamad Irhas; Sulastiana, Marina; Yanuarti, Nurul (IDEA: Jurnal Psikologi, 2025)
Corporate transformation is an inevitability for maintaining relevance and achieving sustainable growth in response to business dynamics. PT X is currently undergoing a transformation process as a national strategic industrial holding company. This study aims to examine the impact of perceived organizational support (POS) on employees’ readiness for change (RFC). The research adopts a quantitative design, employing simple linear regression analysis with a sample of 175 respondents. The findings indicate that POS has a significant effect on RFC, accounting for 19% of the variance. Thus, the support provided by the organization can substantially enhance employees’ preparedness for change, facilitating the company in achieving its transformation objective.